Consumo de antibacterianos en el hospital nacional edgardo rebagliati martins – essalud en el periodo 2007-2009” - Díaz Guanilo, Julio Javier (2010)
We conducted a descriptive, retrospective, cross sectional aim was to determine the characteristics of consumption of antibacterials (ATBs) at the National Hospital Edgardo Rebagliati Martins (HNERM) - EsSalud in the period 2007-2009. Data was evaluated ATBs consumption of all services that are served by the hospital pharmacy HNERM. ATBs total consumption in the period 2007-2009 was 110.17 DDD/100camas-día, being the most widely consumed drug cephalexin (15.49 DDD/100camas-día), followed by norfloxacin (12.41 DDD/100camas-dia) and clindamycin (8.23 DDD/100camas-día). Parenteral ATBs consumption accounted for 39.63% of total consumption, consumption being higher ceftriaxone (6.69 DDD/100camas-día). The 26.48% of total ATBs used were of restricted use, where the highest consumption was Ciprofloxacin (7.22 DDD/100camas-día). The first-generation cephalosporins were the group most widely consumed drug, followed by fluoroquinolones and third generation cephalosporins. The consumption of each of the pharmacological groups of the most widely used ATBs have evolved with statistically significant positive trend (p <0.05); ATBs overall spending during the 2007.2008 and 2009 was S/.3, 061 312, 46; S/.3 457 364, 47 and S/. 4 323 282, 45 respectively.